2014
DOI: 10.1007/s40737-014-0013-2
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving and Help Seeking in First Episode Psychosis: A Qualitative Study

Abstract: The early stages of psychosis pose a frightening and challenging period for their caregivers. In India, the majority of patients with psychosis live with their families, who play an important role in patients' care and treatment. However, their experience in caring persons with psychosis or help-seeking behaviors in the early stages of psychosis is largely unknown. Using a qualitative method, the present study explored the experiences in caring and help-seeking in carers of patients with first episode psychosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Some previous studies too had revealed the practices caregivers adopt to deal with or prevent the aggressive behaviors of their patients, such as close observation, giving advice and reasoning, communication tactics, and taking help from others. [9][10][11] The caregivers experienced emotional disturbances, health issues, financial burden, non-acceptance from society, perceived stigma, and disgrace because of their patient's aggression. Different studies had revealed similar findings-that the aggression had impact on the caregiver's emotional, financial, social, and family functioning, including having to manage disruptions by the patient during family gatherings, stress over decisions to commit the patient to hospitalization, non-acceptance by the society, prejudice, and stigma.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies too had revealed the practices caregivers adopt to deal with or prevent the aggressive behaviors of their patients, such as close observation, giving advice and reasoning, communication tactics, and taking help from others. [9][10][11] The caregivers experienced emotional disturbances, health issues, financial burden, non-acceptance from society, perceived stigma, and disgrace because of their patient's aggression. Different studies had revealed similar findings-that the aggression had impact on the caregiver's emotional, financial, social, and family functioning, including having to manage disruptions by the patient during family gatherings, stress over decisions to commit the patient to hospitalization, non-acceptance by the society, prejudice, and stigma.…”
Section: Original Articlementioning
confidence: 99%
“…A large majority of these studies were conducted in Western countries. [6][7][8][9][10][11][12][13][14][15][16][17] It is difficult to generalize the results to caregivers in India because of cultural differences. Therefore, this study was undertaken to describe the caregivers' experiences of aggression by their family member with schizophrenia.…”
mentioning
confidence: 99%
“…[12] After five decades of research, the EE consistently proved to be detrimental to patients with schizophrenia,[345] mood disorders[67] and eating disorders. [48910] There is some emerging evidence to support its adverse effects in obsessive compulsive disorder (OCD),[11] first episode psychosis (FEP)[512] and substance use disorder. [1314] Apart from its role as regards the outcome of the illness, the EE itself is an indication of a maladaptive coping of the patients' relatives.…”
Section: Introductionmentioning
confidence: 99%
“…The family members provide much-needed care and support including taking day-to-day care, supervising medications, taking the patient to the hospital and looking after the financial needs. [12,32] This active involvement by the family members may occur partly because of the high sense of family responsibility, the value system and family integration, but often is a consequence of an inadequately resourced mental health system. [33] As a result of the increased caregiving tasks, roles and responsibilities, the family caregivers experience significant stress and burden, [12,32] and this could possibly trigger high EE, which in turn may affect the illness outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Persons with severe mental illness experience significant disability in 1 self-care, interpersonal relationship and work. The 2 onset of mental illness in the family can be stressful or 3,4 crisis for the family members. They experience high levels of burden in caring a person with severe mental 5,6 illness.…”
Section: Introductionmentioning
confidence: 99%